Optimization of a regeneration system for Spathoglottis plicata blume orchid from seeds and analysis of its biochemical properties - Mat Yasin, Zaliyatun Akhma (2014)
Spathoglottis plicata is widely used as a ground cover in landscaped garden and as potted plants. Due to its unique structure and colour this orchid is sought after by florists and orchid collectors. However, it is slow growing thus limiting the production of planting materials. Therefore, there is a need to improve its multiplication efficiency and speed up its growth. The objectives of this experiment are to improve the regeneration system of this orchid from the seeds and analyzing its biochemistry properties. The optimizations of the media for the seed germination and callus induction were carried out followed by the development of optimum medium and culture condition for the growth of plantlets and PLBs. The effect of micronutrients on the physical and biochemical changes in plantlets were investigated. In addition, the influences of amino acids and polyamines on the growth and biochemical properties of PLBs were determined followed by the investigation of total phenolic compound in the in vivo and in vitro leaves,roots and PLBs of this orchid. The optimum medium for seed germination was ½ MS augmented with 5 μM BAP. Investigation on the callus induction from seed conducted from various concentration auxin resulted in the highest callus induction were obtained from seed cultured on the medium fortified with 5 μM 2,4-D. The optimum medium and culture condition for plantlets was ½ MS without any plant growth regulator and should be transfered into fresh media after six weeks of culture. Meanwhile, the PLBs should be maintained in the ½ MS supplemented with 5 μM BAP and subcultured after four weeks of culture. Different concentrations of micronutrients give various effects on the physical and biochemical changes in the plantlets. The treatment of 50 μM Zinc had an increase of 50 % in plantlets height but for the treatment of 25 μM Manganese had 60 % increase in the total soluble protein obtained from the plantlet. The presence of micronutrient in the medium also increased the peroxidase and catalase activity but reduced the polyphenol oxidase and nitrate reductase activity in the plantlets. The optimum amino acids concentration for the growth of PLBs was 5 mM glutamine. The addition of 5 mM glutamine and 5 μM BAP improved the growth and increased the peroxidase and catalase activities but reduced the nitrate reductase activity of PLBs. Meanwhile, the optimum polyamine concentration for the growth of PLBs was 25 μM spermidine. The 25 μM spermidine treatment cause a reduction in peroxidase and catalase but increased the nitrate reductase activity in the PLBs. Total phenolic content in vivo leaves and root is higher compared to in vitro and total phenolic content in the PLBs is the lowest.